Development of Digital Comic Learning Media Based Flipbook to Improve Understanding of the Concept of Mutual Cooperation Lifestyle Material Grade IV SDN Ngeni 05 Blitar District - Allatif, Nurlaila; Alfi, Cindya; Fatih, Muhamad (Jurusan Pendidikan Guru Madrasah Ibtidaiyah, 2024)
The aim of this research is to develop learning media, namely flipbook-based digital comics, to improve class IV students' understanding of the concept of mutual cooperation material. The research method uses Research and Development (R&D) research with the ASSURE research model. The instruments used in this research were tests and questionnaires. Tests are used to measure the increase in students' understanding of concepts. Questionnaires are used to measure the validity of media, material, language and product attractiveness. The research results showed an increase in student understanding by 70%. This is proven by the final result of the N-Gain value reaching 0.70 in the “High” category. Meanwhile, the validity results were 80% (material expert), 100% (media expert), 95% (linguist), 87% (product attractiveness).